Analysis of Determination of Human Development Index - Fenty Y. Manuhuttu; Okto Irianto; Esy D. Lewaherilla; Adi Maulana Rachman; Agustinus Fangohoy; Marthen A.I. Nahumury (Bulletin of Community Engagement, 2026)
This study aims to analyze the influence of the Poverty Level and Government Expenditure in Education on the Human Development Index (HDI) in Papua Province. The data used are secondary data taken from 2013 to 2024. The data were analyzed using quantitative methods and multiple linear regression analysis techniques with the help of the SPSS version 21 application. The results of the study indicate that partially the poverty level does not have a significant effect on the Human Development Index with a calculated t value of 1.532 and a t table value of 2.25462 obtained from the t table formula and a significance value of 0.195. If seen the calculated t value <t table and significance value> 0.05. In the variable of government expenditure partially has a significant effect on the human development index with a calculated t value of 10.455 and a t table value of 2.26462 obtained from the t table formula and a significance value of 0.000. If seen the calculated t value> t table and significance value < 0.05. Meanwhile, simultaneously, the variables of poverty level and government spending in the education sector have an influence on the human development index in Papua Province.